2011
DOI: 10.1111/j.1365-2516.2011.02572.x
|View full text |Cite
|
Sign up to set email alerts
|

DDAVP responsiveness in children with mild or moderate haemophilia A correlates with age, endogenous FVIII:C level and with haemophilic genotype

Abstract: In most individuals with moderate/mild haemophilia A, FVIII:C levels increase following DDAVP administration to a haemostatic range, thus avoiding the need for FVIII concentrates. We sought to determine the relationship between responsiveness to DDAVP in boys (<18 years old) with mild/moderate haemophilia and patient age, haemophilic severity and haemophilic genotype. Our cohort consisted of 13 boys with moderate and 61 boys with mild haemophilia who, between them, had 38 different mutations; 21 had unique mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
66
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 25 publications
(35 reference statements)
5
66
1
Order By: Relevance
“…Their small study in n = 8 moderate hemophilia A patients showed that 38% had FVIII:C peak levels ≥ 0.30 IU mL À1 . A recent study by Seary et al [11] reported limited to no response to desmopressin in moderate hemophilia A patients. However, the study was performed in children with a median age of 3.7 years.…”
mentioning
confidence: 96%
“…Their small study in n = 8 moderate hemophilia A patients showed that 38% had FVIII:C peak levels ≥ 0.30 IU mL À1 . A recent study by Seary et al [11] reported limited to no response to desmopressin in moderate hemophilia A patients. However, the study was performed in children with a median age of 3.7 years.…”
mentioning
confidence: 96%
“…Young children often have markedly lower responses to desmopressin than adults, but they may become responsive at an older age. [27][28][29] The FVIII half-life, typically around 6 to 8 hours, is positively associated with basal and peak VWF antigen levels and patient age. 24 Some mutations are consistently associated with favorable responses (in particular, several of those at risk for inhibitor development; Table 1), whereas promoter, splicing, or intronic mutations respond poorly, and some missense mutations show a reduced FVIII survival 3,24-27 ( Figure 1).…”
Section: How To Reduce the Risk For Inhibitor Development In Mhamentioning
confidence: 99%
“…Although there is a certain consistency of the response within the same mutation, the response to desmopressin is somehow heterogeneous. [24][25][26][27]29 Therefore, the individual response should always be assessed by a test infusion of desmopressin with FVIII measured at least 1 and 4 hours after its administration to ascertain the pattern of response and the rate of clearance.…”
Section: How To Reduce the Risk For Inhibitor Development In Mhamentioning
confidence: 99%
“…In a Canadian study of boys with hemophilia in whom the FVIII response initially failed after desmopressin treatment, a response was seen when they were rechallenged after a mean of 6.3 years [8]. Seary et al [9] found, in their study of 74 boys with 38 different mutations causing moderate or mild hemophilia, that age and FVIII level were strong predictors of response to desmopressin. The stronger effect of desmopressin in older patients in our study may reflect the increase in baseline FVIII levels with age, as previously described by Miesbach et al [10], but our model does not completely explain the variation in the effect of DDAVP.…”
mentioning
confidence: 99%
“…While both the plasma-and platelet-derived molecules can form a functional complex, several studies demonstrate that the two cofactor pools are physically and functionally distinct [2][3][4][5][6][7]. Despite these differences, the entire platelet-derived pool of the procofactor, FV, is endocytosed from the plasma by megakaryocytes [4,8] via a two-receptor system consisting of a specific, unknown FV receptor and low density lipoprotein (LDL) receptor-related protein-1 (LRP-1) [9], an endocytic receptor belonging to a superfamily of proteins related to the LDL receptor [10]. Flow cytometric analyses and fluorescence microscopy indicate that all megakaryocytes express LRP-1 [9,11].…”
mentioning
confidence: 99%